(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Shoulders instability and anterior shoulder dislocation is a common problem in adolescents especially athletes and military personnel. Young age is known as most important risk factor of recurrent shoulder dislocation. The concept of "glenoid off-track" claimed to increase risk of shoulder dislocation and failure of treatment so we hypothesized that younger patients with recurrent shoulder dislocation have more rate of glenoid off-track than adult patients.Material and Method: 70 patients including military personnel referred with recurrent shoulder dislocation chose and 3D CT-scan of affected shoulder obtained. Then the expected glenoid diameter, glenoid defect and the Hill-Sachs lesion size measured and patients grouped as glenoid off-track or on-track. All these measurements and being off-track/on-track compared between adults (>25 years old) and adolescents (<25 years old).Results: The mean size of expected glenoid diameter, glenoid defect and Hill-Sachs lesion show no significant difference between adolescent and adult groups, however glenoid off-track cases are significantly more in adolescent group compared to adult group (63.6% vs 37.8% p-value:0.027 CI:95%).Conclusion: Younger patients have significantly more rate of glenoid off-track compared to adult group, which could be the reason of higher rate of recurrent shoulder dislocation and treatment failure in this group of age.